V. O. Key Goes Urban: Toward Understanding a Changing Political Order. Issue 6 (November 2019) - Stone, Clarence N.
A body of recent work shows that the urban political arena and its analysis are undergoing a profound shift. Through a political-order concept inspired by the work of V. O. Key, this essay examines how contextual change and acts of agency combine in forming the governing arrangements that encompass cities. To unpack the change process, the analysis offered here uses a comparison between (1) the prevailing order in the several years following the close of World War II when urban redevelopment and Black mobilization were the dominant struggles and (2) the present time with its seemingly more fluid character but a backdrop of a highly partisan clash of cultures waged intergovernmentally. The comparison between the periods demonstrates the degree to which political orders can vary, with a sturdy order of redevelopment and accommodation giving way to hampered efforts to pursue urban progressivism. Even with a market economy a large presence across time, change follows no master arc but remains configurative.